CBRNE 재난 시 격리이송을 위한 장치 개발에 관한 탐색적 연구 - Ham, Seung Hee; Park, Namkwun; Yoon, Myong O (한국재난정보학회 논문집, 14(1), 2018)
In this study, it is aimed to prevent the spread of pollutants in the event of a major disaster caused by CBRNE accidents and attacks and build up system to provide optimal transport environment for each patient condition By identifying characteristics of existing products and make them immediately applicable in the field. The purpose of this study is suggesting essential consideration in both functional and performance in the development of the isolation unit. As a result of the study, it suggests (1) basic function, (2) efficient field utilization, (3) isolation unit interface and combination of modules in development of isolation unit. 본 연구에서는 CBRNE 사고 및 공격에 의한 대규모 재난 발생 시 오염원 확산을 최대한으로 방지하면서 환자상태별 최적의 이송환경을 제공하기 위한 격리캡슐을 개발하는데 있어 필요한 성능적 기능적 요구사항을 고찰하고자 하였다. 이를 위하여 기존에 개발된 제품들의 특성을 파악함으로써 현장에서 즉각 활용을 어렵게 하는 곤란요소를 보완 수정할 수 있는 방안을 제시하였다. 연구결과, 현장에서 즉각 활용을 용이하게 하기 위한 격리이송장치를 개발하기 위해서 (1)기본기능, (2)효율적인 현장활용성, (3)격리이송장치 인터페이스 및 모듈간 결합방안의 각 고려요소에 대하여 제시하였다.